(untitled) (UNED Research Journal, 2014)
ABSTRACT: Growth inhibitory effects produced by the cypress, Cupressus lusitanica (Cupressaceae) in Bosque de La Hoja, Heredia, Costa Rica. In Costa Rica, Cupressus lusitanica is an introduced tree that may produce negative effects in the plants surrounding it. This study sought to compare light, soil humidity and acidity provided by cypress trees and the effect on the distribution and growth of pioneer and dicotyledonous plants around them in El Bosque de la Hoja, Heredia Province, Costa Rica. There were no differences in soil moisture and acidity at different distances from a cypress tree (acidity was similar to native forest). Monocotyledonous plants grow closer to cypress than dicotyledonous plants, particularly in parts that receive more light, suggesting an allelopathic effect that requires light as a catalyst.Although C. lusitanica could alter the light environment and the soil acidity and moisture, these negative effects could be countered with appropriate management. KEY WORDS: Cupressus lusitanica, soil moisture, soil acidity, special distribution, monocot plant, dicot plant.